The Effect Of Consumption Of Green Bean Juice On Exclusive Breastfeeding Mothers On Infant Weight Gain - Lisviarose; Dezy Mellisa; Meirita Herawati (Journal of Global Research in Public Health, 2023)
The prevalence of exclusive breastfeeding tends to decrease in general due to the desire of parents for rapid growth of their baby's weight, especially the promotion of formula milk which is increasingly intensive. Breast milk is the single best source of nutrition for babies because it contains Fats, Carbohydrates, proteins, Vitamins, Minerals, Water and natural protective substances that can protect babies against various diseases. Green beans are one of the lagtogogum plants that contain vitamin tiamin and polyphenols that can increase breast milk production.   The purpose of this study was to determine the effect of giving green bean juice on infant weight gain in breastfeeding mothers exclusively breastfed. Quasy experimental type of research with pretest and  post test design with nonequivalent control group design. The study was conducted from September to November 2020 in the Working Area of UPT Puskesmas Sebangar Bengkalis Regency with a population of 189 mothers having babies aged (0-6) months with a total sample of 32 people, purposive sampling technique. Giving green bean juice is done once a day as much as 300 ml for 14 consecutive days. Data processing using an independent sample t test. From the results of the study, the average weight gain of babies in the experimental group was 468.74 grams while the average weight gain of the control group babies was only 290.62 grams.  In the independent test of the t-test sample, a p value = 0.021 was obtained, where the p value of ≤ 0.05 Ha was received, meaning that there was an effect of giving mung bean juice on infant weight gain in breastfeeding mothers exclusively in the Working Area of UPT Sebangar Health Center, Bengkalis Regency. It is recommended that breastfeeding mothers can consume Green Bean Juice to help smooth milk production, so as to increase baby weight gain in exclusive breastfeeding mothers.